2001
DOI: 10.1161/hh1001.091447
|View full text |Cite
|
Sign up to set email alerts
|

New Tricks for Old Dogs

Abstract: Abstract-Thrombin is a serine protease that potently activates platelets and catalyzes the conversion of fibrinogen to fibrin. Thrombin also exerts direct effects on vascular cells, such as smooth muscle cells, via interactions with members of the protease-activated receptor family. Evidence in several animal models implicates thrombin-mediated signaling events in the response to injury that typifies vascular lesion formation in atherosclerosis and restenosis. In this review, we examine the activation of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(18 citation statements)
references
References 151 publications
(109 reference statements)
1
17
0
Order By: Relevance
“…Thrombin also activates a variety of cell types, including endothelial cells, smooth muscle cells, and leukocytes (40,41); for example, thrombin induces leukocyte adhesion to endothelial cell surface by increasing the cell surface expression of adhesion molecules ICAM-1, VCAM-1, P-selectin, and E-selectin (18,42,43). Thrombin promotes the expression of ICAM-1 and VCAM-1 via the activation of the transcription factor NF-B in endothelial cells (18,37,42).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin also activates a variety of cell types, including endothelial cells, smooth muscle cells, and leukocytes (40,41); for example, thrombin induces leukocyte adhesion to endothelial cell surface by increasing the cell surface expression of adhesion molecules ICAM-1, VCAM-1, P-selectin, and E-selectin (18,42,43). Thrombin promotes the expression of ICAM-1 and VCAM-1 via the activation of the transcription factor NF-B in endothelial cells (18,37,42).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin also exerts direct effects on cells to regulate platelet aggregation, endothelial cell activation, and smooth muscle cell (SMC) 1 proliferation via interactions with members of the protease-activated receptor (PAR) family, such as PAR1, PAR2, PAR3, and PAR4, known as G-protein-coupled receptors (2,3). However, the intracellular signaling cascades downstream from the thrombin receptors are surprisingly complex and are still not well understood.…”
mentioning
confidence: 99%
“…PAR-1, PAR-2, PAR-3 and PAR-4 have been identified. 13) Vascular smooth musle cell (VSMC) are known to express PAR-1, PAR-2, and PAR-4 thus potentiating the effect of thrombin in the activation of VSMC proliferation and migration. 14) Previous report has showed that PAR-1 activation on EPC promoted the 3 steps of angiogenesis, including proliferation, migration, and differentiation.…”
Section: Discussionmentioning
confidence: 99%